Statblithz Game Media Development to Train Students' Mathematical Problem-Solving Skills - Ani Afifah; Alya Wulandari; Rani Darmayanti; Paulo Vitor da Silva Santiago; Samuel Karim (JTAM (Jurnal Teori dan Aplikasi Matematika), 2026)
Mathematical problem-solving skills are essential for students to succeed in the 21st century, yet many struggle to apply mathematical concepts in real-life situations. This research addresses the need for innovative learning media by developing Statblithz Game, an educational game designed to train and enhance students’ mathematical problem-solving abilities. The study employed a Research and Development approach using the ADDIE model, involving stages of analysis, design, development, implementation, and evaluation. Participants included middle school students who engaged with the prototype and provided feedback through questionnaires, expert validations, and pre- and post-tests measuring problem-solving performance. The results indicated that Statblithz Game is highly feasible, with expert validation scores averaging 89%. Moreover, students’ problem-solving test scores improved by an average of 25% after using the game. In conclusion, the Statblithz Game effectively enhances mathematical problem-solving skills and offers an engaging alternative to traditional mathematics instruction. The impact of this research lies in providing educators with an innovative and interactive tool that can foster critical thinking and improve student learning outcomes in mathematics.